Absorbable Organic Halide (AOX) Reduction in Elemental Chlorine-Free (ECF) Bleaching of Bagasse Pulp from the Addition of Sodium Sulphide - Shuangxi Nie; Shuangquan Yao; Shuangfei Wang; Chengrong Qin (BioResources, 2015)
A laboratory investigation was developed to confirm and to quantify the reductions in absorbable organic halide (AOX) discharge when sodium sulphide was added during elemental chlorine-free (ECF) bleaching of sugarcane bagasse pulp. After the chlorine dioxide bleaching stage, the pulp was sent directly into the extraction stage without washing. FTIR was employed to determine the breakage of chemical bonds in the pulp, and GC-MS was used to measure the composition of the bleaching effluent. The addition of sodium sulphide caused a reduction in AOX of up to 46.7%. The AOX reduction reached this maximum when the sodium sulphide was added 30 min after the start of the extraction stage and when the pH was higher than 12. FTIR spectroscopy showed that the phenolic lignin of the pulp was degraded by the sodium sulphide and that the syringyl lignin and C-O-C, C=O structure of the pulp holocellulose of the pulp was preserved during the extraction stage. The GC-MS showed that the chlorobenzene and chlorophenol contents decreased noticeably after the addition of sodium sulphide.